The impact of environmental enrichment on energy metabolism in ovariectomized mice - Chaoran Ju; Ayano Ogura; Yoshikazu Hayashi; Yuko Kawabata; Fulvio D’Acquisto; Tomoyo Kawakubo-Yasukochi; Eijiro Jimi (PLoS ONE, 2025)
After menopause, a decline in ovarian function leads to various physical and psychological changes, potentially resulting in a range of pathological conditions, including abnormalities in energy metabolism. In recent years, environmental enrichment, which is characterized by positive and comfortable eustress, has been shown to improve various physiological and pathological conditions. This study investigated the effects of environmental factors on energy metabolism in a menopause model using an ovariectomized (OVX) mouse model. Wild-type female mice (8-week-old) were subjected to OVX or a sham operation and maintained under standard condition (SC), enriched environment (EE), or isolated (IS) condition for 4 weeks. OVX led to weight gain and disruption of circadian rhythms, along with changes in various metabolic parameters influenced by differences in housing environments; i.e., EE improved metabolic parameters, but IS deteriorated them. Physical activity and social interaction were factors that determined these differences. Menopause is usually a significant transitional period in a woman’s life, and changes in the social environment during this period can contribute to a diverse range of physical and psychological symptoms. Consequently, when implementing interventions to alleviate menopause-related pathological conditions, not only physical symptoms but also the social context should be carefully considered.